Studies on the respiration rate of free and immobilized cells of Cephalosporium acremonium in cephalosporin C production - Araujo, M. L.G.C. [UNESP]; Giordano, R. C.; Hokka, C. O. (My University, 1999)
Bioprocesses using filamentous fungi immobilized in inert supports present many advantages when compared to conventional free cell processes. However, assessment of the real advantages of the unconventional process demands a rigorous study of the limitations to diffusional mass transfer of the reagents, especially concerning oxygen. In this work, a comparative study was carried out on the cephalosporin C production process in defined medium containing glucose and sucrose as main carbon and energy sources, by free and immobilized cells of Cephalosporium acremonium ATCC 48272 in calcium alginate gel beads containing alumina. The effective diffusivity of oxygen through the gel beads and the effectiveness factors related to the respiration rate of the microorganism were determined experimentally. By applying Monod kinetics, the respiration kinetics parameters were experimentally determined in independent experiments in a complete production medium. The effectiveness factor experimental values presented good agreement with the theoretical values of the approximated zero-order effectiveness factor, considering the dead core model. Furthermore, experimental results obtained with immobilized cells in a 1.7-L tower bioreactor were compared with those obtained in 5-L conventional fermentor with free cells. It could be concluded that it is possible to attain rather high production rates working with relatively large diameter gel beads (ca. 2.5 mm) and sucrose consumption-based productivity was remarkably higher with immobilized cells, i.e., 0.33 gCPC/kg sucrose/h against 0.24 gCPC/kg sucrose/h in the aerated stirred tank bioreactor process.

Bioprocesses using filamentous fungi immobilized in inert supports present many advantages when compared to conventional free cell processes. However, assessment of the real advantages of the unconventional process demands a rigorous study of the limitations to diffusional mass transfer of the reagents, especially concerning oxygen. In this work, a comparative study was carried out on the cephalosporin C production process in defined medium containing glucose and sucrose as main carbon and energy sources, by free and immobilized cells of Cephalosporium acremonium ATCC 48272 in calcium alginate gel beads containing alumina. The effective diffusivity of oxygen through the gel beads and the effectiveness factors related to the respiration rate of the microorganism were determined experimentally. By applying Monod kinetics, the respiration kinetics parameters were experimentally determined in independent experiments in a complete production medium. The effectiveness factor experimental values presented good agreement with the theoretical values of the approximated zero-order effectiveness factor, considering the dead core model. Furthermore, experimental results obtained with immobilized cells in a 1.7-L tower bioreactor were compared with those obtained in 5-L conventional fermentor with free cells. It could be concluded that it is possible to attain rather high production rates working with relatively large diameter gel beads (ca. 2.5 mm) and sucrose consumption-based productivity was remarkably higher with immobilized cells, i.e., 0.33 gCPC kg sucrose/h against 0.24 gCPC/kg sucrose/h in the aerated stirred tank bioreactor process.
Keywords: Ca-alginate oxygen diffusivity; Cephalosporin C production; Effectiveness factor; Immobilized cells; Reaction-diffusion model